2010
DOI: 10.1002/prep.200900002
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Crystallization of Submicrometer Energetic Compounds

Abstract: This study introduces the conception of an apparatus to crystallize continuously nanosized explosive or more generally nanosized organic materials. These materials can be elaborated in pure state or in form of mixtures of energetic and inert materials. The installation can produce nano‐RDX or nano‐PETN from 1 to 10 g h−1 using a reactor containing one ultrasonic piezoelectric transducer.The present study describes the different parameters which influence the crystallization process. It presents first results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…The basic conversion processes taking place at those heterogeneities can be summed up to [2,3]: Depending on their particular position, inside or outside of the explosive particle, hot-spots are classified into internal and external hot-spots [4]. By aiming for the elimination of hot-spots, two basic approaches to desensitize explosives emerged over the past years: First, reducing the size and number of intercrystalline defects, unwanted inclusions or voids by a slow and controlled recrystallization of the explosive or second by decreasing the particle size of the ex-plosive thus far that the formation of intercrystalline heterogeneities is unlikely to appear [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The basic conversion processes taking place at those heterogeneities can be summed up to [2,3]: Depending on their particular position, inside or outside of the explosive particle, hot-spots are classified into internal and external hot-spots [4]. By aiming for the elimination of hot-spots, two basic approaches to desensitize explosives emerged over the past years: First, reducing the size and number of intercrystalline defects, unwanted inclusions or voids by a slow and controlled recrystallization of the explosive or second by decreasing the particle size of the ex-plosive thus far that the formation of intercrystalline heterogeneities is unlikely to appear [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This might be because more time was required for processing larger batches which gives time for particles to grow in size than reported solvent-antisolvent based processes used for nanoscale HNS production which used very small quantity of~1.3 g HNS per batch [11]. Similarly, very small batch size varying from 0.25 to 1 g or millimolar dilute concentrations of other explosives like HMX, RDX and CL-20 have been reported to be used to achieve their preparation in nanosize [18][19][20][21][22][23][24][25][26]. Moreover, open literature provides little information on whether nano-size HNS will be produced even on increasing the batch size.…”
Section: Particle Size and Morphologymentioning
confidence: 99%
“…Several promising effects of nanostructured energetic materials have been revealed, for instance, less sensitivity to external stimuli and higher performances [1,2].P revious studies have shown that sensitivity of nitramine explosives (e.g. RDX, HMX,a nd CL-20) is intensely affected by their individual particle size distribution [3,4].B yd ecreasing the particle size of an explosive, the formation of intracrystalline heterogeneities (voids, crystallographic defects, gaseous or liquid inclusions, and impurities) is reduced, and consequently the formationo f" hot spots", which start the accidental ignition reaction chain, can be suppressed.F or this reason, many recent studies in the literature were focused on the productiono fe nergeticn anomaterials,s uch as n-RDX [5][6][7],n-HMX [8][9][10],a nd n-CL-20 [ 11,12].…”
Section: Introductionmentioning
confidence: 99%